2004
DOI: 10.1097/01.don.0000125877.26495.69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pitch Length on the Behavior of Rotary Triple Helix Root Canal Instruments

Abstract: The behavior of nickel-titanium instruments depends largely on the cross-section of the working part. The effect of pitch length was evaluated using two instruments with the same cross-section (triple helix; 0.6% taper). One had a short pitch (0.5 mm at the tip to 0.9 mm at 16 mm at the end of the working part). The other had a long pitch (1.18 mm/2 mm). A dynamometer recorded tensional stress (MHz) and the tendency to screw in (Fz) during simulated canal preparations. Rotational speed was kept constant, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 9 publications
3
55
1
3
Order By: Relevance
“…These results may be explained by their different cross-sectional designs; whereas R has a double-cutting edge S-shaped geometry, WO has a modified, convex, triangular cross-section with radial lands at the tip, and a convex triangular cross-section in the middle and coronal portion of the file, with a larger cross-sectional area when compared to R. 20 This larger cross-sectional area influences the bending resistance of the instrument, 23 making it less flexible and thus increasing the straightening trend in curved canals. The larger cross-sectional area of PTN and PTU may also substantiate the differences between these and R. In addition, other variables such as the screw-in effect, which usually occurs with active instruments that rotate under continuous rotation motion, 24,25 and the total number of used instruments, may explain the results obtained by PTN and PTU herein. Overall, PTU system showed the highest canal transportation mean (0.082 mm), which may be explained by its traditional NiTi alloy, which noticeably affects stress-strain distribution patterns and bending ability, making PTU much less flexible.…”
supporting
confidence: 53%
“…These results may be explained by their different cross-sectional designs; whereas R has a double-cutting edge S-shaped geometry, WO has a modified, convex, triangular cross-section with radial lands at the tip, and a convex triangular cross-section in the middle and coronal portion of the file, with a larger cross-sectional area when compared to R. 20 This larger cross-sectional area influences the bending resistance of the instrument, 23 making it less flexible and thus increasing the straightening trend in curved canals. The larger cross-sectional area of PTN and PTU may also substantiate the differences between these and R. In addition, other variables such as the screw-in effect, which usually occurs with active instruments that rotate under continuous rotation motion, 24,25 and the total number of used instruments, may explain the results obtained by PTN and PTU herein. Overall, PTU system showed the highest canal transportation mean (0.082 mm), which may be explained by its traditional NiTi alloy, which noticeably affects stress-strain distribution patterns and bending ability, making PTU much less flexible.…”
supporting
confidence: 53%
“…Mtwo has sharp blade and negative rake angle, ProTaper � has sharp blade and positive rake angle while K3 TM has unique asymmetrical radial land and slightly positive rake angle. Therefore, positive rake angle may be related to the screw-in 270 Diemer and Calas 20) stated that a varying helical angle and a longer pitch may help in preventing screw-in. Their explanation was that a longer pitch reduces the helical angle, which in turn considerably reduces screw-in.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Cross-sectional geometry, helical angles, pitch length and taper of files are included in these factors. 16 Diemer et al evaluated the effect of pitch length on the torsional stress and tendency to screw-in using two instruments with same cross-section (triple helix; 6% taper). 16 Their results showed that increasing the pitch length decreased torsional load sharing and the tendency to screw-in.…”
Section: Introductionmentioning
confidence: 99%
“…16 Diemer et al evaluated the effect of pitch length on the torsional stress and tendency to screw-in using two instruments with same cross-section (triple helix; 6% taper). 16 Their results showed that increasing the pitch length decreased torsional load sharing and the tendency to screw-in. Schräder et al compared torques and forces developed by two sequences of nickel-titanium rotary instruments, using only .04 taper instruments or a combination of .04 and .06 tapers, respectively.…”
Section: Introductionmentioning
confidence: 99%